Chemical and pharmaceutical evaluation of the relationship between triazole linkers and pore size on cyclodextrin–calixarene nanosponges used as carriers for natural drugs. Issue 56 (24th May 2016) - Massaro, M.; Cinà, V.; Labbozzetta, M.; Lazzara, G.; Lo Meo, P.; Poma, P.; Riela, S.; Noto, R.
Abstract : Nanosponges based nanocarriers with three different cavities were used to encapsulate and release bioactive compounds. Abstract : Mixed cyclodextrin–calixarene nanosponges were used to prepare some composites with the well known polyphenolic bioactive compounds quercetin and silibinin. The composites were characterized by means of different techniques (UV-vis, FT-IR, microcalorimetry, thermogravimetry), in order to assess their loading and thermal stability. The kinetics of release of the bioactive molecules into aqueous solution were studied at two different pH values (1.0, 6.4), which mimic typical physiological conditions. Finally the possible antiproliferative effects in vitro were assayed towards three triple negative breast cancer cell lines (SUM 149, SUM 159 and MDA-MB-23). Our results point out the role assumed by the triazole linkers, present in the nanosponge network, in affecting both the adsorption abilities of the materials towards the bioactive molecules, and the antiproliferative activity of the composites. This work puts forward an efficient strategy to prepare nanosponge based nanocarriers with three different cavities that could encapsulate two or more drug molecules with different physico-chemical properties.